Microwave nondestructive testing of composite materials low frequency range (50 - 2000 MHz) / Rafidah Abdul Malik - Abdul Malik, Rafidah (1995)
A study has been made on microwave nondestructive testing (NDT) that was used to test nonconducting and semiconductors materials especially composite materials. These materials such as plastics, wood and rubber were measured by MODEL 6409 RF NETWORK ANALYZER that operates in the low frequency range of 10 - 2000 MHz. Coaxial slotted line has been used as sample holder or transmission line. Transmission and reflection test methods have been used to measure the sample characteristics. The purpose of this work is to find the transmission loss, return loss and power absorption coefficient (PAC).